2017
DOI: 10.1115/1.4036832
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Degradation Modeling of Ocean Steel Structures Using Bayesian Network

Abstract: Modeling depth of long-term pitting corrosion is of interest for engineers in predicting the structural longevity of ocean infrastructures. Conventional models demonstrate poor quality in predicting the long-term pitting corrosion depth. Recently developed phenomenological models provide a strong understanding of the pitting process; however, they have limited engineering applications. In this study, a novel probabilistic model is developed for predicting the long-term pitting corrosion depth of steel structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Then the long-term corrosion takes place, which is led by biological activities and nutrients in seawater [117]. Some researchers have shown that the duration of short-term and long-term corrosions depends on the constituents of seawater (biological and chemical) and its physical properties, temperature in particular [118].…”
Section: **mentioning
confidence: 99%
See 2 more Smart Citations
“…Then the long-term corrosion takes place, which is led by biological activities and nutrients in seawater [117]. Some researchers have shown that the duration of short-term and long-term corrosions depends on the constituents of seawater (biological and chemical) and its physical properties, temperature in particular [118].…”
Section: **mentioning
confidence: 99%
“…The standard fluctuation of pH in seawaters lies between 7.8 and 8.2 and it has been reported by several researchers that this variation does not have significant impact on corrosion rate. However, it can indirectly influence accumulation of calcium carbonate on cathode protected structures [118,144]. The pH variations may exert an active influence on pitting and crevice corrosion of active-passive metals [145].…”
Section: Physical and Chemical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 218,219 ] Recently, the BN model was found to be effective in estimating the system/product reliability of complex systems, such as high‐speed trains, [ 219 ] solar‐powered unmanned aerial vehicles, [ 220 ] and pitting degradation structural steel in marine systems. [ 221 ]…”
Section: System Level Reliability Of Light‐emitting Diodesmentioning
confidence: 99%
“…[218,219] Recently, the BN model was found to be effective in estimating the system/product reliability of complex systems, such as high-speed trains, [219] solar-powered unmanned aerial vehicles, [220] and pitting degradation structural steel in marine systems. [221] In this section, a BN method that considers the intricacies of the high-power LED lamp system and the functional interaction among components for reliability assessment and lifetime prediction is briefly introduced. This approach considers the parametric (degradation based) and catastrophic failure modes of each component in order to assess the system level reliability, and it also requires the design of experiments to gather the required data.…”
Section: System Level Reliability Of Light-emitting Diodesmentioning
confidence: 99%